Anti-warping and anti-aging plastic floor base material, floor and preparation method
The combination of PETG resin, ABS resin and activated eloite/calcium carbonate composite powder was prepared, which solved the problem of insufficient light and thermal expansion performance of PETG floors and achieved low curvature of the floor Quhe high comprehensive performance.
Patent Information
- Application Number
- CN202411844911.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing PETG floor cannot meet the floor usage requirements in terms of lighting and thermal expansion performance, and the PETG/ABS alloy is complex and not suitable for use as a floor substrate, making it difficult for the floor to achieve comprehensive performance of low warpage and anti-aging.
The combination of PETG resin, ABS resin, activated elolite/calcium carbonate composite powder, compatible agent, chain extender, coupling agent, lubricant, antioxidant and light stabilizer is used, and after acidification treatment and ultrasonic blending Double screw extrusion prepares anti-warming and anti-aging plastic floor substrates, and makes floors with a six-layer material structure.
Improves the overall performance of the floor, including low warpage, flatness, toughness and thermal expansion resistance, reduces cracking and heat shrinkage, and enhances the stability and durability of the floor.
Smart Images

Figure CN119286208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high molecular polymer floor materials, and in particular relates to an anti-warping and anti-aging plastic floor substrate and a floor and a preparation method thereof. Background Art
[0002] PVC flooring is the most widely used plastic flooring at present, but it has problems such as high recycling cost and dioxin generation when directly incinerated. With the introduction of environmental protection concepts such as "Non-PVC" and "PVC-Free" in recent years, the application of non-PVC materials such as PP and PE in the home building materials industry has continued to expand. Research and development of safe, environmentally friendly and durable non-PVC flooring is the main trend of future technological development.
[0003] PET material (polyethylene terephthalate), also known as Polyethylene terephthalate in English, has the advantages of being non-toxic, odorless, safe, environmentally friendly and recyclable. However, PET is a semi-crystalline polymer with strong macromolecular aggregation ability and poor impact resistance, which cannot meet the requirements of elastic plastic flooring. There are currently a small number of studies on PET flooring, such as patent documents CN110029796A and CN114571821A. PETG (polyethylene terephthalate-1,4-cyclohexanedimethyleneterephthalate), the full English name: polyethylene terephthalate-I, 4-cyclohexanedimethyleneterephthalate, is a transparent, non-crystalline copolyester. However, compared with existing PVC elastic plastic floors, PETG cannot meet the actual use requirements of floors in terms of light and thermal expansion performance. Parameters such as dimensional stability still need to be improved. There are a small number of documents that use PETG for flooring, such as patent document CN115139616A (PETG is used as a scratch-resistant layer and a glass fiber layer is used), CN219706385U (PETG is only used as a film layer), CN214329733U (PETG is made together with a carbon fiber sheet layer and a polyphosphate sheet), CN212453480U (PETG is only used as a wear-resistant layer), CN112064977A (PETG is only used as a wear-resistant layer and a decorative layer, and the substrate layer is an MDI flame-retardant fiberboard), and CN112009060A (PETG is used as a wear-resistant layer, a decorative layer, and a substrate layer).
[0004] ABS resin (Acrylonitrile Butadiene Styrene) is a thermoplastic polymer material with high strength, good toughness and easy processing. Due to its high strength, corrosion resistance and high temperature resistance, it is often used to manufacture plastic shells of instruments. However, ABS also has the problem of easy warping, such as CN109206832A.
[0005] There are research reports on the use of PETG / ABS alloy in the preparation of rubber for ship fenders, computer display housings, etc., such as CN105482274A, CN109535634A, etc., but the materials are complex and not suitable for use as floor substrates. Currently, there are no research reports and performance reports on the use of PETG / ABS alloy for flooring. Summary of the invention
[0006] In view of the above problems, the purpose of the present invention is to provide a warping and aging-resistant plastic floor substrate and a floor and a preparation method, which has the properties of low warping that are difficult to achieve with ordinary floors, thereby improving the comprehensive performance of the floor.
[0007] The technical solution of the present invention includes: Firstly, the invention provides an anti-warping and anti-aging plastic floor substrate, which is made of the following materials in parts by weight: 40-60 parts of PETG resin, 10-30 parts of ABS resin, 2-10 parts of compatibilizer, 150-200 parts of activated halloysite / calcium carbonate composite powder, 0.4-2 parts of chain extender, 0.4-1.5 parts of coupling agent, 1-3 parts of lubricant, 0.5-1.5 parts of antioxidant, and 0.1-2 parts of light stabilizer, wherein the activated halloysite / calcium carbonate composite powder is obtained by heating and activating acidified halloysite, mixing it with calcium carbonate in water, and filtering and drying it after ultrasonic treatment.
[0008] Preferably, when preparing the activated halloysite / calcium carbonate composite powder, the mass ratio of halloysite to calcium carbonate is 1:(1-4).
[0009] Preferably, the compatibilizer is one or more of AS-g-MAH, SEBS-g-GMA, POE-g-GMA, and ABS-g-MAH, and more preferably POE-g-GMA.
[0010] Preferably, the chain extender is one or more of epoxies, oxazolines, isocyanates, and acid anhydrides; more preferably, it is one or more of 2,2-(1,3-phenylene)-bis(2-oxazoline) (PBO, oxazolines), triglycidyl isocyanurate (TGIC, isocyanates), and pyromellitic dianhydride (PMDA, anhydrides).
[0011] Preferably, the coupling agent is one or more of aluminate, phosphate, and titanate, and more preferably one or two of aluminate and titanate.
[0012] Preferably, the lubricant is one or more of zinc stearate, erucic acid amide, ethylene bis stearamide (EBS), and mineral white oil, and more preferably EBS.
[0013] Preferably, the antioxidant is one or more of hindered phenols, aromatic amines, phosphites, and sulfur-containing esters. More preferably, it is one or more of antioxidant 1010 (hindered phenols), antioxidant 5057 (aromatic amines), antioxidant 626 (phosphites), and ditridecyl thiodipropionate (DTDTP, sulfur-containing esters).
[0014] Preferably, the light stabilizer is one or more of carbon black, benzophenones (such as BASF Chimassorb 81), acetanilide (such as Sanduvor VSU), benzotriazole (such as UV-320) or triazine (such as UV-1164). More preferably, carbon black is used.
[0015] Secondly, the present invention provides a method for preparing the aforementioned plastic floor substrate, comprising the following steps: S1: The halloysite is acidified with hydrochloric acid, and then heated and activated at 60° C. for 8 h. The acidified halloysite and calcium carbonate are then added into pure water and mixed, ultrasonically treated for 2 h, filtered, dried, and the activated halloysite / calcium carbonate composite powder is obtained.
[0016] S2: Place activated halloysite / calcium carbonate composite powder, PETG resin, ABS resin, compatibilizer, chain extender, lubricant, coupling agent, antioxidant and light stabilizer in a high-speed mixer and stir at a speed of 300-350 r / min for 10-20 min; extrude the obtained mixture by twin-screw extrusion, and the temperatures of each zone of the twin-screw are 200-190°C, 195-190°C, 190-180°C, 185-175°C, 180-170°C, and the confluence core temperature is 170-160°C; shape and thickness are determined to obtain the plastic floor substrate.
[0017] Again, the present invention provides a floor prepared using the aforementioned plastic floor substrate, which is made of six layers of materials, and the six layers of materials are arranged in the following order: a first coating layer, a transparent film layer, a color film layer, an anti-warping and anti-aging plastic floor substrate layer, a second coating layer, and a sound-absorbing layer.
[0018] Preferably, the color film layer and the transparent film layer are both made of PETG; Preferably, the thickness of the plastic floor substrate layer is 4.1-4.2 mm; Preferably, the color film thickness of the color film layer is 1 mm; Preferably, the transparent film layer has a thickness of 2 to 3 mm.
[0019] Preferably, the first coating layer and the second coating layer are made of polyurethane-acrylic resin coating; Preferably, the sound absorbing layer is selected from radiation cross-linked polyethylene (IXPE) sound-absorbing pad or radiation cross-linked polypropylene (IXPP) sound-absorbing pad.
[0020] The beneficial effects of the present invention include: In the plastic floor substrate of the present invention, PETG has good structural regularity and high flatness; ABS has good toughness, but ABS is prone to shrinkage and warping due to thermal stress during the molding process. PETG and ABS are blended to form an alloy, which can take into account both the flatness and toughness of the material. In addition, the activated halloysite / calcium carbonate obtained by potential adsorption of halloysite activated by acidification and hydroxyl groups on the surface of calcium carbonate as a filler can improve the strength of the PETG / ABS floor substrate, reduce warping, and reduce defects such as cracking of the floor. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a cross-sectional schematic diagram of a low-warping, anti-aging PETG / ABS plastic floor product of the present invention; In the figure, 1 is the first coating layer, 2 is the transparent film layer, 3 is the color film layer, 4 is the anti-warping and anti-aging plastic floor substrate layer, 5 is the second coating layer, and 6 is the sound-absorbing layer. DETAILED DESCRIPTION
[0022] In order to better illustrate the purpose, technical scheme and effect of the present invention, the present invention is further described below in conjunction with specific embodiments.It should be understood that specific embodiments are only used to explain the present invention and are not used to limit the scope of protection of the present invention.The materials used in the following examples are all conventional materials sold on the market.If no additional instructions are given, the sources of materials with the same name, specifications, etc. in the following examples are all the same.Wherein PETG resin, ABS resin, POE-g-GMA and other compatibilizers, PMDA and other chain extenders, EBS and other lubricants are purchased from Henan Yinjinda New Materials Co., Ltd., Taiwan Chimei Industrial Co., Ltd., Jiayirong Polymer (Shanghai) Co., Ltd., Jiangsu Hualun Chemical Co., Ltd., and Xingbeida Chemical Materials Co., Ltd.
[0023] The following experimental samples and comparative samples were prepared by the following method. The plastic floor substrate was fed according to the ingredients shown in Tables 1 and 2. The specific steps are as follows: S1: The halloysite is acidified with hydrochloric acid, and then heated and activated at 60° C. for 8 h. The acidified halloysite and calcium carbonate are then added into pure water and mixed, ultrasonically treated for 2 h, filtered, dried, and the activated halloysite / calcium carbonate composite powder is obtained.
[0024] S2: Place activated halloysite / calcium carbonate composite powder, PETG resin, ABS resin, compatibilizer, chain extender, lubricant, coupling agent, antioxidant and light stabilizer in a high-speed mixer and stir at a speed of 300-350 r / min for 10-20 min; extrude the obtained mixture by twin-screw extrusion, and the temperatures of each zone of the twin-screw are 200-190°C, 195-190°C, 190-180°C, 185-175°C, 180-170°C, and the confluence core temperature is 170-160°C; shape and thickness are determined to obtain the plastic floor substrate.
[0025] S3: Follow Figure 1 The structure of the plastic floor substrate is conventionally coated with PETG color film and PETG transparent film online, coated and tempered, punched and slotted, and coated with IXPE mute pad to make the floor product. The first coating layer 1 and the second coating layer 5 are polyurethane-acrylic resin coatings.
[0026] As test samples, the floor sizes and thicknesses of the following embodiments and comparative examples are the same (the thickness of the anti-warping and anti-aging plastic floor substrate layer is 4.1 mm; the thickness of the PETG color film layer is 1 mm; the thickness of the PETG transparent film layer is 2 mm).
[0027] Example 1 Preparation of floor substrate and floor Table 1 Ingredients of experimental sample floor substrate (parts by weight)
[0028] Table 2 Comparative sample floor base material ingredients (parts by weight)
[0029] Table Notes: Comparative Sample A 5 did not use halloysite or activated halloysite (replaced with an equal amount of calcium carbonate), and step S1 was not required in the preparation. Comparative Sample B 6 activated halloysite was replaced with an equal amount of unactivated halloysite, and step S1 did not include the halloysite acidification treatment and heating activation steps.
[0030] Example 2 Performance testing and comparison of floor samples The experimental samples and comparative samples prepared in Example 1 were subjected to the following performance tests, and the test reference standards and methods were as follows: Warpage test: Tested in accordance with ISO24342 standard. Cut the sample into a 250mm×250mm square, place it on a flat table, and use a feeler gauge to test the four corners of the sample one by one. The test result is the maximum value of the four corners. The warpage is required to be ≤1.2mm.
[0031] Heat shrinkage test: Tested in accordance with ISO24342 standard. The sample is cut into a 250mm×250mm square, and the length and width of the sample are measured (all four sides need to be measured and recorded, the length is L10, L20, and the width is W10, W20). The sample is placed in an 80℃ oven, taken out after 6 hours and placed in the laboratory for 3 hours. After the static state, the length and width of the sample are tested (the length is L11, L21, and the width is W11, W21). Calculation, length: {[(L10+L20) / 2-(L11+L21) / 2] / [(L10+L20) / 2]}×100%; width: {[(W10+W20) / 2-(W11+W21) / 2] / [(W10+W20) / 2]}×100%, and the maximum value is selected for the test result. The heat shrinkage rate is required to be ≤0.12%.
[0032] Wheelchair test: Tested in accordance with EN425 standard. The sample is slotted into a U-shaped buckle or vertical buckle, cut into a specific shape for splicing, and the spliced sample is fixed on the wheelchair tester, and different rotations are set for testing. The wheelchair test is required to be ≥25,000 rotations.
[0033] Thermal expansion test: Cut a 180mm×1220mm sample, place it in a drying room, and set the drying room temperature to 20℃. After the drying room reaches the set temperature, keep it warm for 3h, measure the length and width, and record the length as L10 and L20, and the width as W10 and W20. Then set the drying room temperature to 70℃, keep it warm for 3h after reaching the set temperature, measure the length and width, and record the length as L11 and L21, and the width as W11 and W21. Calculate the experimental data, the thermal expansion coefficient of length is: {[(L11+L21) / 2-(L10+L20) / 2] / [(L10+L20) / 2] / 50}×100000; the thermal expansion coefficient of width is: {[(W11+W21) / 2-(W10+W20) / 2] / [(W10+W20) / 2] / 50}×100000, and the maximum value is selected for the test result. The thermal expansion coefficient is required to be ≤6.
[0034] Cracking test: Tested in accordance with EN13329 standard. Take a 300mm×250mm sample and place it on the bottom plate of the drop ball impact tester, fix it with screws, and drop a 2280g ball from a height of 1500mm for impact test. No cracking is required by the drop ball impact.
[0035] Lighting test: Cut a sample of 180mm×1220mm, place it in a lighting laboratory, set the lighting temperature to 70℃, and light for 3 hours. It is required that there is no arching phenomenon after lighting.
[0036] Elastic modulus and static bending strength test: Test according to GB17657 standard. Cut 50mm×150mm samples, measure the sample thickness, place the samples on the support rollers of the universal mechanical testing machine, input the sample thickness and then test. The elastic modulus is required to be ≥3500MPa and the static bending strength is ≥18MPa.
[0037] Table 3 Performance test data of experimental samples 1 to 6
[0038] Table 4 Performance test data of comparative samples 1 to 6
[0039] The test results of the above samples show (Table 3, Table 4) that the floors of experimental samples 1-6 have better anti-warping performance, wheelchair test results, thermal expansion coefficient, cracking test and arching than the comparative samples; the thermal shrinkage rate is lower than that of comparative samples 1 to 4, etc.; the elastic modulus and static bending strength are higher than those of comparative samples 1 and comparative samples 3 to 6. The comprehensive performance of the floor samples of the present invention is better than that of the comparative samples.
[0040] From the analysis of the experimental results, the factors affecting floor warping, cracking, and arching are complex. After PETG and ABS are compounded, the anti-warping effect can be improved by adjusting the ingredients, but there is a problem of floor cracking. Although there is no cracking in comparative examples 1 and 2, there are problems such as arching. The use of activated halloysite combined with ingredient adjustment has an important contribution to solving the cracking problem.
[0041] The above embodiments are only some of the preferred solutions of the present invention and do not limit the present invention in any form. Without exceeding the description of the specification, based on the overall concept of the present invention, simple replacement / conversion solutions that can be obtained by those skilled in the art without creative labor should still be regarded as the protection scope of the present invention.
Claims
1. A warping and aging resistant plastic floor substrate, characterized in that: The plastic floor substrate is made of the following materials by weight: 40-60 parts of PETG resin, 10-30 parts of ABS resin, 2-10 parts of compatibilizer, 150-200 parts of activated halloysite / calcium carbonate composite powder, 0.4-2 parts of chain extender, 0.4-1.5 parts of coupling agent, 1-3 parts of lubricant, 0.5-1.5 parts of antioxidant, and 0.1-2 parts of light stabilizer, wherein the activated halloysite / calcium carbonate composite powder is obtained by heating and activating acidified halloysite, blending it with calcium carbonate in water, and filtering and drying it after ultrasonic treatment.
2. The anti-warping and anti-aging plastic floor substrate according to claim 1, characterized in that: When preparing the activated halloysite / calcium carbonate composite powder, the mass ratio of halloysite to calcium carbonate is 1:(1-4).
3. The anti-warping and anti-aging plastic floor substrate according to claim 1, characterized in that: The compatibilizer is one or more of AS-g-MAH, SEBS-g-GMA, POE-g-GMA, and ABS-g-MAH.
4. The anti-warping and anti-aging plastic floor substrate according to claim 1, characterized in that: The chain extender is one or more of epoxies, oxazolines, isocyanates and acid anhydrides.
5. The anti-warping and anti-aging plastic floor substrate according to claim 1, characterized in that: The coupling agent is one or more of aluminate, phosphate and titanate.
6. The anti-warping and anti-aging plastic floor substrate according to claim 1, characterized in that: The lubricant is one or more of zinc stearate, erucic acid amide, ethylene bis stearamide, and mineral white oil.
7. The anti-warping and anti-aging plastic floor substrate according to claim 1, characterized in that: The antioxidant is one or more of hindered phenols, aromatic amines, phosphites, and sulfur-containing esters.
8. The anti-warping and anti-aging plastic floor substrate according to claim 1, characterized in that: The light stabilizer is one or more of carbon black, benzophenones, acetanilides, benzotriazoles or triazines.
9. The method for preparing a warping and aging resistant plastic floor substrate according to claim 1, characterized in that: The steps include: S1: acidifying the halloysite with hydrochloric acid, then heating and activating at 60° C. for 8 h, then adding the acidified halloysite and calcium carbonate into pure water, mixing, ultrasonically treating for 2 h, filtering, drying, and obtaining activated halloysite / calcium carbonate composite powder; S2: Place activated halloysite / calcium carbonate composite powder, PETG resin, ABS resin, compatibilizer, chain extender, lubricant, coupling agent, antioxidant and light stabilizer in a high-speed mixer and stir at a speed of 300-350 r / min for 10-20 min; extrude the obtained mixture by twin-screw extrusion, and the temperatures of each zone of the twin-screw are 200-190°C, 195-190°C, 190-180°C, 185-175°C, 180-170°C, and the confluence core temperature is 170-160°C; shape and thickness are determined to obtain the plastic floor substrate.
10. A composite floor prepared by using the anti-warping and anti-aging plastic floor substrate according to any one of claims 1 to 8 or the anti-warping and anti-aging plastic floor substrate prepared by the preparation method according to claim 9, characterized in that: The composite floor is made of six layers of materials, and the six layers of materials are arranged in the following order: a first coating layer, a transparent film layer, a color film layer, an anti-warping and anti-aging plastic floor substrate layer, a second coating layer, and a sound-absorbing layer.
11. The composite flooring according to claim 10, characterized in that: The color film layer and the transparent film layer are both made of PETG.
12. The composite flooring according to claim 10, characterized in that: The thickness of the anti-warping and anti-aging plastic floor substrate layer is 4.1-4.2 mm.
13. The composite flooring according to claim 10, characterized in that: The color film layer has a color film thickness of 1 mm.
14. The composite flooring according to claim 10, characterized in that: The thickness of the transparent film layer is 2-3 mm.
15. The composite flooring according to claim 10, characterized in that: The first coating layer and the second coating layer are made of polyurethane-acrylic resin coating; the sound-absorbing layer is selected from radiation cross-linked polyethylene sound-absorbing pad or radiation cross-linked polypropylene sound-absorbing pad.
Citation Information
Patent Citations
High-performance rubber for ship fender
CN105482274A
ABS material with extremely-low warpage and no cracking and for 3D printing, and preparation method thereof
CN109206832A
Spray-free antibacterial ABS / PETG alloy and preparation method thereof
CN109535634A
Environment-friendly, abrasion-resistant and scraping-resistant PET floor
CN110029796A
Environment-friendly floor and manufacturing process thereof
CN112064977A
Cited By
High-strength heat-resistant flame-retardant floor base material based on regenerated PETG (polyethylene terephthalate glycol) and preparation method thereof
CN121293699A
Heat-insulating high-strength plastic floor and preparation method thereof
CN121295891A